UPAYA MENINGKATKAN PEMAHAMAN DAN MOTIVASI BELAJAR SISWA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI SANGGAR BELAJAR MUHAMMADIYAH KEPONG MALAYSIA - Sukamto, Mey Suryani; Ismail shaleh Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At the Muhammadiyah Kepong Learning Center in Malaysia, the Contextual Teaching and Learning (CTL) approach was used in this project to improve students' understanding and motivation to learn. This two-cycle study employed a descriptive qualitative approach and Classroom Action Research (CAR) techniques. Twenty sixth-grade students served as subjects. Tests, questionnaires, interviews, and observations were all used as data collection methods. Based on the results, students' understanding of learning increased from an average of 65.5 in cycle I to 78.2 in cycle II when the CTL strategy was used. From a sufficient category (2.3) in cycle I to a high category (3.1) in cycle II, students' enthusiasm for learning also increased. Between cycles I and II, learning completion increased from 60% to 85%. Students' active engagement in the learning process increased and learning became more relevant when learning materials were connected to their real-world experiences through the use of the CTL method.